The Effectiveness of Multisensory Stimulation Therapy in People with Specific Language Disorder - Siregar, Iskandarsyah (Budapest International Research and Critics University, 2022)
People with language disorders are also ordinary people who still want to communicate and be understood by others. Of course, the conditions and shortcomings that they experience become a challenge for themselves and for others who interact with them. The conditions and weaknesses that they experience become a challenge for themselves and others who interact with them. Problems or speech disorders experienced by people with specific language disorders caused by brain damage are obstacles to children's social and personal adjustment. People with particular language disorders caused by brain damage who mispronounce words will feel embarrassed and begin to isolate themselves from other people. This study tries to explain the impact of the learning method based on Multisensory Stimulation therapy and then evaluates the results of the application of Multisensory Stimulation therapy in patients with Transcortical Aphasia. This research uses a crossbreed approach that uses qualitative and quantitative perspectives reciprocally. The type of research used is classroom accomplish research. This study concludes that the learning method based on Multisensory Stimulation therapy has a significant positive impact. However, the development of strategies, tactics, and learning models based on Multisensory Stimulation also needs to be developed, actualized, and coordinated according to the principles of effectiveness and efficiency.